Customisable Bundling Approach for Online Supermarkets using Association Rules of Product Categories - Nair, Vani V; V, Vedashree; BK, Vimala; Srinivas, Chetana; M, Yamuna (International Journal of Computer Sciences and Engineering, 2025)
This research deals with the identification of customers and their buying behavior patterns. The aim is to sell the products which are least preferred by the customers so as to make a cost-effective sale by using bundling approach. A Customized bundling is a group of resources joined together in a single package that has an associated logical name. A bundle is a collection of products which are sold together for a single price. It is the well organized way to make the customer’s shopping self-satisfied. It is implemented by the integration of associative clustering and Support vector machine (SVM) with java.